2018
DOI: 10.1364/oe.26.006639
|View full text |Cite
|
Sign up to set email alerts
|

Laser acceleration of absorbing particles

Abstract: A Yb-doped fiber laser is used to accelerate and evaporate absorbing particles in air. Optical intensities of 1MW/cm and 2MW/cm illuminate stainless steel particles. These particles are accelerated to velocities of tens of meters per second before evaporating within a few tenths of a millisecond. Position measurements are made using direct imaging with a high-speed camera. A fundamental system of coupled differential equations to track particle momentum, velocity, mass, radius, temperature, vapor opacity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…To calculate the heat flux from the particle into the film via contact conductance, the temperature of the particle must be known in addition to that of the film. The evaporating particle is assumed to stabilize at its sublimation temperature of 4000 K 19 , as previous studies with evaporating contaminants have shown the temperature gradient across such a particle to be minimal 20 . Modeling heat flux between the particle and surface was done using MATLAB’s partial differential equation toolbox.…”
Section: Resultsmentioning
confidence: 99%
“…To calculate the heat flux from the particle into the film via contact conductance, the temperature of the particle must be known in addition to that of the film. The evaporating particle is assumed to stabilize at its sublimation temperature of 4000 K 19 , as previous studies with evaporating contaminants have shown the temperature gradient across such a particle to be minimal 20 . Modeling heat flux between the particle and surface was done using MATLAB’s partial differential equation toolbox.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we have demonstrated how breaking the symmetry of the well-known counter-propagating optical trapping system can modify the overall optical forces leading to increased trapping stability and allowing for long-range particle trapping and manipulation in liquid media. While there are numerous reports on long-range particle manipulation via optical tweezers, most of them are performed in gas or vacuum media and mainly rely on thermophoretic forces [29,44,45]. Here we trap and manipulate a broad range of particles with different sizes and shapes, including microorganisms, with the use of radiation pressure forces and without creating standing waves [22] or thermal effects.…”
Section: Discussionmentioning
confidence: 99%
“…For metal particles, the forces exerted by the diffraction fringes repel them to leave the traps. For the absorbing particles, the laser heating of particles results in a strong thermal gradient that drives the particles to leave the diffraction fringes [35][36][37]. Plasmonic tweezers may be a suitable method to assemble the metal or absorbing particles [38][39][40][41].…”
Section: Forming Steady Patterns Of Particles In a Salt Solutionmentioning
confidence: 99%